Pengaruh Jenis Media Tanam Dan Pemberian Pupuk Organik Cair Terhadap Pertumbuhan Tanaman Anggrek (Dendrobium sp): media tanam, konsentrasi, pupuk organik cair, anggrek - Widiastuti, Aprilia Putri; Ratna Nurhayati, Dewi; Bahri, Saiful (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
In this research, to determine the type of planting media with the right concentration of liquid organic fertilizer on the growth of orchid plants (Dendrobium sp) is the aim of the research entitled The Effect of Planting Media Type and Application of Liquid Organic Fertilizer on Orchid Plants (Dendrobium sp). The research ware conducted at Raja Bunga Anggrek Jl Jimbaran No. 18 in Coblong, Pakopen, Bandungan, Semarang Regency, Central Java, between November 2023 and January 2024. This study used a completely randomized design with two treatment factors and three replications. The first factor is the planting medium (M) with three levels, namely black moss (M2), white moss (M1), and fern (M3). The second factor is liquid organic fertilizer (P) with three levels, namely without treatment, 0ml/liter (P0), 10ml/liter (P2), 15ml/liter (P3). Data was analyzed using analysis of variance with the Least Significant Difference (LSL) test 5% level. The parameters observed were plant height (cm), leaf length (cm), number of roots and number of shoots. Based on the results of the research and discussion, it can be concluded that the black moss planting media type shows the best results in the growth of orchids (Dendrobium sp) and the right liquid organic fertilizer at 10 ml/liter.